Cinemas múltiplos: notas sobre a diversidade na linguagem cinematográfica - SILVA, Dayana Manasses Ribeiro (2024)
From an analysis of the classic cinematography of Hollywood - taken as a reference of a normalization of the "making movies" - in contrast to the proposals of "subversion" of that language, of which the experimental cinema and avant-garde cinema, we can verify characteristics which reveal the diversity of cinematographic languages. The present text proposes to elaborate on this diversity as a field of possibilities of transformation of the classic cinematographic device. At first, the text focuses on the "cinematographic norm" pointing some of its aspects under the light of authors like Erwin Panofsky and Ernest Cassirer. In a second part, the research focuses on the use of counter-discourse and the beginning of a cinematic corporeity that is opposed to the domination of the classical approach of cinema. Finally, the text develops aspects of the expansion of language and the dilution of the cinematographic device.